Partners in Health - Centre for Access to Services in English (CASE) (2022)
Number of pages: 3

Concert de Noël : Chants et souvenirs de Noël - Centre for Access to Services in English (CASE) (2022)
Parallel title: Christmas Concert: Carols and Christmas Memories

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2022)
Number of pages: 1

Stories of a Small “Shtetl” : Jewish History in Drummondville - Miller, Julie (2022)

Money Raised for La Rose des Vents de Drummond and a Successful First Edition of the “History and Music” Concert Series - Centre for Access to Services in English (CASE) (2022)

The Tourist Offer of the Whiteley Museum and its Surrounding Area on the Lower North Shore : A Quality Improvement Report - Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
This report analyzes the tourist offer in the eastern part of Quebec’s Lower North Shore, particularly the municipality of Bonne-Espérance, a region where English speakers make up the majority of the population. It focuses specifically on an institution in one of these municipalities, the Whiteley Museum. The report provides the authors’ suggestions to improve tourism development as a means to diversify the economy, potentially help reverse demographic decline, and build community vitality.

Concert Series to Highlight Talents of Young Musicians Celebrating Local Heritage in the Sonorous Acoustics of St George Anglican Church - Centre for Access to Services in English (CASE) (2022)

The Effects of the Pandemic on the Arts & Creative Sector in Québec : How Anglophone Artists, Creators, and Performers are Faring in a Time of Adversity - Eraso, Cecilia (Youth for Youth Québec (Y4Y Québec), 2022)
The arts, entertainment, and recreation sector is infamous for being in a state of constant flux. The experience of consecutive short-term contracts and annual seasonal employment terminations is a familiar reality for many creators, producers, and performers in Québec (Jeannotte, 2021). What is unique for some Québec artists is the experience of a linguistic divide in the provincial arts sector. In 2016, English-speaking artists in the province earned less than their Francophone counterparts, on average, making a median income of “85 cents for every $1 made by Francophone artists’’ (Hill, 2020). On the national level, statistics from the 2016 Canadian Census show that Anglophone artists from Québec have a lower median income than the rest of Canadian artists. These findings are especially surprising when considering that, nationally, English-speakers in Québec represent a significant portion of Canadian artists. Anglophones in Québec account for 4.6% of all Canadian artists, despite only representing 2.8% of the Canadian labour force (Hill, 2020). The data indicate that two factors, occupation and language, are related to discrepancies in income levels in Québec.

COVID-19 Update - Quebec Drama Federation (QDF) (2022)

A New Confinement That Will Leave Its Mark - Morse, Rachel; Régnier, Laurence (2022)

ArtistsInspire Grants COVID-19 Protocol - English Language Arts Network (ELAN); Leading English Education and Resource Network (LEARN) (2022)

Elementary School Workshop Catalogue : 2022-2023 School Year - English Language Arts Network (ELAN); Leading English Education and Resource Network (LEARN) (2022)

High School Workshop Catalogue : 2022-2023 School Year - English Language Arts Network (ELAN); Leading English Education and Resource Network (LEARN) (2022)

Society Pages - Morrin Centre (2022)
Number of pages: 32

Society Pages - Morrin Centre (2022)
Number of pages: 32

QDF's Membership & Community Summit Schedule - Quebec Drama Federation (QDF) (2022)

Annual Report - Vision Gaspé-Percé Now (2022)